Ground Water Quality Assessment of Rural Area of Deoli Tehsil, Tonk District (Rajasthan) with Special Reference to Fluoride Analysis - Meena, K.S.; Gunsaria, R.K.; Meena, Kanta; Kumar, N.; Meena, P.L.; Meena, R.R. (Asian Journal of Chemistry, 2012)
High rates of mortality and morbidity due to water-borne diseases are well known in India. Serious degradation of water quality in urban India has often been attributed to indiscriminate disposal of sewage and industrial effluents into surface water bodies. The population in rural India is mainly dependent on the groundwater as a source of drinking water. As a quality concern the groundwater is often found to be contaminated with fluoride, arsenic, iron and salts. In recent years, fluorosis has emerged as major public health issue in rural India. This paper briefly presents the water quality special focus on fluoride. One hundred thirty samples were collected from different villages of Deoli Tehsil, (Tonk), Rajasthan during the month of May-June 2009 in clean polyethylene bottles. Samples were analyzed for different parameters such as- pH, total alkalinity (TA), fluoride (F–), nitrate (NO3–), total dissolved solids, chloride (Cl–), total hardness, electrical conductivity, Ca-H, Mg-H, CO3–2, HCO3–, Na+ and K+ by using standard techniques. The results revealed that the most of the water samples were below or beyond limits, according to the WHO standards (1996). The F– concentration ranged 0.30 to 9.60 ppm. Minimum (0.30 ppm) and maximum (9.60 ppm) concentration of F– was observed from Jalseena and Akodiya villages respectively. The drinking water of Deoli Tehsil is not potable, proper treatment of groundwater is suggested prior to its use for drinking purpose. Removal of fluoride from drinking water is suggested through various defluoridation techniques are available including quick reverse osmosis, electrodialysis and hit and trial method.